1993
DOI: 10.1007/bf00012864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought and root injury on plant-generated CS2 emissions in soil

Abstract: Conditions under which some plants emit carbon disulfide (CS2) in the soil are unknown. A pot assembly was constructed to measure soil CS 2 emissions by Mimosa pudica under conditions of undisturbed growth, root injury, and drought stress. When M. pudica was grown without disturbance, soil CS 2 emissions were below the limit of detection (~<0.1 ngCS2 mL -I) for the entire 8-wk sampling period. However, when the roots of 6-wk-old M. pudica plants were cut to a depth of 10cm, a maximum of 0.5 and 0.4ngCSzmL -I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…In the course of these studies and in agreement with previous reports (Hartel and Reeder, 1993;Piluk et al, 1998), we detected a pungent, unpleasant sulfurous odor when 7-d-old gnotobiotically grown plants were dislodged from soil. However, more often than not, it was also observed that, when left undisturbed, neither seedlings germinated in soil nor plants germinated aseptically on agar exhibited an odor detectable to the human subjects performing the experiments.…”
Section: Pudica Roots Emit An Odor When Exposed To Certain Stimulisupporting
confidence: 92%
See 4 more Smart Citations
“…In the course of these studies and in agreement with previous reports (Hartel and Reeder, 1993;Piluk et al, 1998), we detected a pungent, unpleasant sulfurous odor when 7-d-old gnotobiotically grown plants were dislodged from soil. However, more often than not, it was also observed that, when left undisturbed, neither seedlings germinated in soil nor plants germinated aseptically on agar exhibited an odor detectable to the human subjects performing the experiments.…”
Section: Pudica Roots Emit An Odor When Exposed To Certain Stimulisupporting
confidence: 92%
“…S5). This implies that these compounds, when observed previously by GC-MS, were artifacts of the experimental protocol used for their detection (Haines et al, 1989;Farkas et al, 1992;Hartel and Reeder, 1993;Feng and Hartel, 1996;Piluk et al, 1998).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations